Lamin A/C and polymeric actin in genome organization - Ondřej, Vladan; Lukášová, Emilie; Krejčí, Jana; Matula, Pavel; Kozubek, Stanislav (Molecules and Cells, 2008)
In this work, we have studied the structural and functional linkage between lamin A/C, nuclear actin, and organization of chromosome territories (CTs) in mammary carcinoma MCF-7 cells. Selective down-regulation of lamin A/C expression led to disruption of the lamin A/C perinuclear layer and disorganization of lamin-bound emerin complexes at the inner nuclear membrane. The silencing of lamin A/C expression resulted in a decrease in the volume and surface area of chromosome territories, especially in chromosomes with high heterochromatin content. Inhibition of actin polymerization led to relaxation of the structure of chromosome territories, and an increase in the volumes and surface areas of the chromosome territories of human chromosomes 1, 2 and 13. The results show an important role of polymeric actin in the organization of the nuclei and the chromosome territories.
Keywords: financování organizované; tvar buňky; genom lidský; Cell Line, Tumor; Chromosomes, Human; Lamin Type A; lidé; Cell Nucleus; lamin typ A; Cell Shape; Financing, Organized; buněčné jádro; Down-Regulation; aktiny; Actins; lidské chromozomy; down regulace; Genome, Human; Microscopy, Confocal; konfokální mikroskopie; nádorové buněčné linie; Humans